Community rebuilding processes in a disaster-damaged area through community currency: The pilot project of Domo in Kamaishi, Japan. Issue 1 (6th February 2017) - Nakazato, Hiromi; Lim, Seunghoo
Abstract : Purpose: Community currency (CC) is used as a tool for reviving local communities by promoting economic growth and facilitating the formation of social capital. Although the Japanese CC movement has stagnated since mid-2005, a new experiment, Fukkou Ouen Chiiki Tsuka (CC for supporting disaster recovery), was introduced across disaster-damaged areas after the Great East Japan Earthquake and tsunami of March 2011. Previous studies assessing the role of CC in these earthquake-damaged areas are rare; the purpose of this paper is to examine the micro processes of community rebuilding that underlie the transactional networks mediated by one of the experiments, Domo, in Kamaishi. Design/methodology/approach: Using transactional records capturing residents' CC activities during the five-month pilot period before actual implementation of Domo simultaneous investigation for empirical network analysis techniques identify the network configuration dynamics representing the multiple observed forms of social capital in this disaster-affected local community. Findings: This study of the five-month pilot for the Domo system revealed: intensive dependence on the coordinating role of core members (i.e. the creation of weak ties), a lack of balanced support among members and the resulting uni-directional transactions (i.e. the avoidance of generalized exchanges), and the reinforcement of previous transactional ties via reciprocation or transitive triads (i.e. the formation of strong ties). Originality/value: This study provides guidance for practitioners, researchers, and policy makers on how community residents' engagement in CC activities could function as a potential tool for generating positive socio-economic effects for local communities in disaster areas.